2014
DOI: 10.1128/iai.00086-14
|View full text |Cite
|
Sign up to set email alerts
|

PafR, a Novel Transcription Regulator, Is Important for Pathogenesis in Uropathogenic Escherichia coli

Abstract: The metV genomic island in the chromosome of uropathogenic Escherichia coli (UPEC) encodes a putative transcription factor and a sugar permease of the phosphotransferase system (PTS), which are predicted to compose a Bgl-like sensory system. The presence of these two genes, hereby termed pafR and pafP, respectively, has been previously shown to correlate with isolates causing clinical syndromes. We show here that deletion of both genes impairs the ability of the resulting mutant to infect the CBA/J mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 62 publications
3
16
0
Order By: Relevance
“…Based on their results, they suggested a unique role for bgl in the host. Along this line, the results of our recent study of the paf operon in UPEC indicated that it is an in vivoinduced operon, that is, its expression is induced only in the host [Baum et al, 2014]. Importantly, some of the genes whose expression has been affected upon expression of the PafR antiterminator in UPEC [Baum et al, 2014] contain a putative RAT identified by our medium descriptor, e.g.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Based on their results, they suggested a unique role for bgl in the host. Along this line, the results of our recent study of the paf operon in UPEC indicated that it is an in vivoinduced operon, that is, its expression is induced only in the host [Baum et al, 2014]. Importantly, some of the genes whose expression has been affected upon expression of the PafR antiterminator in UPEC [Baum et al, 2014] contain a putative RAT identified by our medium descriptor, e.g.…”
Section: Discussionsupporting
confidence: 54%
“…Along this line, the results of our recent study of the paf operon in UPEC indicated that it is an in vivoinduced operon, that is, its expression is induced only in the host [Baum et al, 2014]. Importantly, some of the genes whose expression has been affected upon expression of the PafR antiterminator in UPEC [Baum et al, 2014] contain a putative RAT identified by our medium descriptor, e.g. dmsA and c4647, the first is active under anaerobic conditions and the second overlaps with bglG but is expressed from the other strand, whereas others, such as all genes of the mal regulon, are controlled by a transcription factor whose respective gene contains a putative RAT, malt in this case.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations